In Vitro Digestibility of Lamtoro Leaves (Leucaena Leucocephala) In Poultry With Gizzard Fluid And Duodenum - Tri Ambarwati; Ali Mursyid Wahyu Mulyono; Engkus Ainul Yakin (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2021)
Protein source feed is the feed that has the biggest share in the nutritional needs of livestock. Lamtoro or Leucaena leucocephala is one of the leaf flours that can be used as an alternative feed ingredient for poultry in the tropics. With its abundant availability and does not compete for its needs with humans and has no selling value so that it can minimize consumption costs for poultry. This study aims to determine the effect of fluid from the digestive tract of chickens on the in vitro digestibility measurement of lamtoro leaves. The study used a completely randomized design (CRD) with a unidirectional pattern with 4 treatments and 3 replications. The treatments consisted of P0 = control, P1 = gizzard fluid, P2 = duodenal fluid and P3 = a mixture of gizzard and duodenal fluid. The results of this study show the average Dry Matter Digestibility Coefficient (%) for the treatment P0, P1, P2 and P3 respectively; 19.276, 29.089, 20.515 and 28.737. Organic Matter Digestibility Coefficient ; 27.702, 36.313, 24.795 and 35.649. Dissolved Protein Digestibility Coefficient ; 39.777, 53.288, 21.145 and 48.737. The results of the statistical test that the administration of lamtoro leaves showed a significant difference (P<0.05) on the digestibility coefficient of dry matter, organic matter and dissolved protein. The conclusion is that the use of gizzard liquid is more effective in increasing the in vitro digestibility of lamtoro leaves.